1981
DOI: 10.1097/00000658-198108000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Myocardial Infarction Following Carotid Endarterectomy

Abstract: Routine coronary angiography has been recommended to all patients undergoing carotid endarterectomy at the Cleveland Clinic since 1978. Patients found to have severe, correctable coronary artery disease (CAD) have been advised to undergo myocardial revascularization as a staged or combined procedure in conjunction with carotid endarterectomy in an attempt to reduce the incidence of fatal myocardial infarction during the postoperative period, and during the late follow-up interval. In order to provide an histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

1981
1981
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(14 citation statements)
references
References 15 publications
2
10
0
2
Order By: Relevance
“…It is obvious that some patients in this study might not benefit from surgery, as high peri-operative cardiovascular risk and poor late survival are expected [13,14,26,27]. CAD is the most important cause of perioperative complications and death in patients undergoing carotid endarterectomy [18][19][20][21]. In this study, the prevalence rate of concurrent CAD was very high.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…It is obvious that some patients in this study might not benefit from surgery, as high peri-operative cardiovascular risk and poor late survival are expected [13,14,26,27]. CAD is the most important cause of perioperative complications and death in patients undergoing carotid endarterectomy [18][19][20][21]. In this study, the prevalence rate of concurrent CAD was very high.…”
Section: Discussionmentioning
confidence: 80%
“…The surgical risk in patients with coexisting coronary and carotid stenosis is significantly increased, whether a staged approach or simultaneous combined coronary bypass grafting and carotid endarterectomy is chosen [29][30][31][32]. Considering the high concurrent rate of multi-vessel or left main CAD in our series, endovascular treatment for the carotid stenosis might be a safe and effective option [18][19][20][21][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that some patients with cerebral ischemia and no overt CAD have evidence of asymptomatic CAD on provocative tests (i.e. myocardial perfusion imaging or exercise ECG) for myocardial ischemia [22, 23, 24, 25]. This association is seen especially in patients with large-artery cerebrovascular disease rather than those with penetrating artery disease or cryptogenic stroke [26].…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative end points included neurologic deficit, death, and cardiac complications de¬ fined as (1) requiring admission to, the intensive care unit and requiring specific therapy; (2) new ventricular arrhythmia for which the patient required treatment and for which the patient was not previously treated; and (3) myocardial infarction (MI) diagnosed by standard electrocardiographic criteria, elevation of creatine kinase with MB isozyme fraction over 5%, and an appropriate clinical picture. The patients were followed up a mean of 522 ±280 days after carotid surgery.…”
Section: Methodsmentioning
confidence: 99%